Work, Industry and Canadian Society - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1988)
This article reviews the book, "Work, Industry and Canadian Society," by Harvey J. Krahn & Graham S. Lowe.

Labour-Management Cooperation in Canada - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1988)
This article reviews the book, "Labour-Management Cooperation in Canada," by Craig W. Riddell.

The Tyranny of Work Alienation and the Labour Process - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1988)
This article reviews the book, "The Tyranny of Work: Alienation and the Labour Process," by James W. Rinehart.

Participative Systems at Work : Creating Quality and Employment Security - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1988)
This article reviews the book, "Participative Systems at Work : Creating Quality and Employment Security," by Sidney P. Rubinstein.

Workplace Innovation in Canada. Reflections on the Past Prospects for the Future. - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1988)
This article reviews the book, "Workplace Innovation in Canada. Reflections on the Past Prospects for the Future," by Jacquie Mansell.